COMPARISON OF ACCURACY OF THREE-UNIT ZIRCONIA FIXED PARTIAL DENTURES MADE FROM CONVENTIONAL AND DIGITAL IMPRESSIONS – IN VITRO STUDY - Gogushev , K.; Abadzhiev , M.; Valcheva, Z. (EurasianUnionScientists, 2021)
ABSTRACTINTRODUCTION: Nowadays, the improvement of intraoral scanning systems aims to overcome some limitations of the conventional methods and to eliminate the mistakes that can be made during the production technology and to achieve a more precise design of prosthetic restorations [7]. AIM: The aim of the present study is to evaluate and compare the marginal adaptation and the internal fit of zirconium dioxide fixed partial dentures, made by direct and indirect digital approach.MATERIALS AND METHODS: To perform the in vitro study, a model-sample of the upper jaw was used, on which two artificial plastic teeth 24 and 26 were prepared and tooth 25 was removed. 30 virtual models were created from the prepared model. To obtain the virtual models in the first group (CIS group), 10 conventional impressions (n = 10) were taken with additive silicone impression material using a two-stage two-phase impression technique with a standard metal impression tray. For the second group (PCS group) the conventional impressions were casted wtih IV class high quality hard plaster. The ten digital impressions from the third group (ISG group) were obtained using an intraoral TRIOS scanner.RESULTS: The highest mean value in P1 was measured in the CIS group (155.1 ± 69.96 µm), followed by the PCS group (135.62 ± 78.7 µm). The highest mean value in P2 was obtained in the CIS group (138.32 ± 63.08 µm), followed by the ISG group (117.2 ± 32.48 µm). The highest mean value in point P3 was found in the CIS group (94.525 ± 23.03 µm), while the highest mean value in point P4 was measured in the PCS group (86.34 ± 26.99 µm).CONCLUSION: The obtained mean values regarding the marginal adaptation in all studied groups are within the clinically acceptable range. The highest values in terms of the marginal adaptation indicator were obtained in the PCS group, and the lowest - in the ISG group.